Efficient water oxidation using an Fe-doped nickel telluride–nickel phosphide electrocatalyst by partial phosphating. Issue 23 (30th May 2022) - Tang, Yu-Jia; Zou, Yan; Zhu, Dongdong
Abstract : A facile partial phosphating strategy is reported to prepare an Fe-doped NiTe–Ni12 P5 catalyst on a nickel foam substrate using an Fe-doped NiTe nanosheet array precursor. Fe-NiTe–Ni12 P5 shows remarkable OER activity and stability in an alkaline electrolyte due to the synergistic effects among Fe-doping, NiTe, Ni12 P5 and the newly formed γ-NiOOH, which enable high explosion of active sites, well-modulated electronic structures, and promoted mass/charge transfer. Abstract : Developing transition-metal-based electrocatalysts for the oxygen evolution reaction (OER) with enhanced activities is a feasible strategy to enable the renewable energy conversion. We report here an Fe-doped nickel telluride–nickel phosphide composite (Fe-NiTe–Ni12 P5 ) in situ grown on a nickel foam (NF) substrate. Using a partial phosphating treatment of an Fe-doped NiTe nanosheet array precursor, the as-prepared Fe-NiTe–Ni12 P5 composite demonstrates superior OER electrocatalytic performance with a lower overpotential, smaller Tafel slope, and satisfactory long-term stability in comparison to the benchmark RuO2 and recently reported transition-metal-based catalysts. The physical characterization studies suggest that a dense γ-NiOOH nanosheet layer is formed on the surface of Fe-NiTe–Ni12 P5 after the OER. Due to the synergistic effects among Fe-doping, NiTe, Ni12 P5, and the newly formed γ-NiOOH species, a high proportion of the accessible active sites are exposed, and the electronic structure of the catalyst is well modulated to optimize the binding strengths of OER intermediates, while the mass/charge transfer can also be promoted, thereby contributing to enhanced OER results. This work provides a simple and effective strategy for the design of highly active and stable OER electrocatalysts with multi-components by partial phosphating.